Sistem Informasi Layanan Kesehatan Surakarta Berbasis Web - Rumantyo, Kiky Valentina, Nurgiyatna, S.T., M.Sc Ph.D (2016)
Health care information system is a web-based information systems using web or internet technology to support and facilitate the job and the search for information to be more easily and efficiently. Currently, there is provided an information system that provides information about health services in Surakarta in an integrated way. Therefore, this study aims to create an information system (website) to facilitate the public in search of information hospitals and health centers in Surakarta. Making this website using PHP programming language and MySQL as well as its user interface using HTML and CSS. The end result of this system is a website with a variety of features that can facilitate the public to obtain information about the profile of the City Health Office, information hospitals and clinics in Surakarta, feature login and register, searching and maps. System testing is done by using a questionnaire to the public, health care IT, and the Health Department of Health Surakarta. The test results with questionnaires from 25 respondents obtained results of the assessment by 88.8% stating that this information system deserve to be published. This indicates that the website is functioning and running well.